Cynaroside ameliorates methotrexate-induced enteritis in rats through inhibiting NLRP3 inflammasome activation - Lang, Wuying; Wen, Xin; Zhang, Shuangqi; Liang, Xuhua; Chen, Lin; Zhang, Dezhu; Zhou, Ruina; Ali, Ihsan; Hu, Xuansheng; Zhang, Haihua; Cheng, Min (Frontiers in Immunology, 2024)
Introduction Cynaroside exhibits various biological properties, including anti-inflammatory, antiviral, antitumor, and cardioprotective effects. However, its involvement in methotrexate (MTX)-induced intestinal inflammation remains inadequately understood. Thus, we investigated the impact of cynaroside on MTX-induced intestinal inflammation and its potential mechanisms. Methods To assess the protective potential of cynaroside against intestinal inflammation, Sprague-Dawley rats were subjected to a regimen of 7 mg/kg MTX for 3 days, followed by treatment with cynaroside at varying doses (10, 20, or 40 mg/kg). Histopathological evaluations were conducted alongside measurements of inflammatory mediators to elucidate the involvement of the NLRP3 inflammasome in alleviating intestinal inflammation. Results Administration of 7 mg/kg MTX resulted in decreased daily food intake, increased weight loss, and elevated disease activity index in rats. Conversely, treatment with cynaroside at 20 or 40 mg/kg ameliorated the reductions in body weight and daily food intake and suppressed the MTX-induced elevation in the disease activity index. Notably, cynaroside administration at 20 or 40 mg/kg attenuated inflammatory cell infiltration, augmented goblet cell numbers and lowered serum levels of tumor necrosis factor-α, interleukin (IL)-1β, and IL-18, as well as the CD68-positive cell rate in the intestines of MTX-induced rats. Furthermore, cynaroside downregulated the expression levels of NLRP3, cleaved caspase 1, and cleaved IL-1β in MTX-induced rats. Discussion Collectively, our findings indicated that cymaroside alleviates intestinal inflammatory injury by inhibiting the activation of NLRP3 inflammasome in MTX-induced rats.